2008
DOI: 10.1007/s00246-008-9247-7
|View full text |Cite|
|
Sign up to set email alerts
|

Balloon Dilation of the Pulmonary Valve in Premature Infants with Tetralogy of Fallot

Abstract: Infants with tetralogy of Fallot (ToF) presenting with desaturation may require augmentation of the pulmonary blood flow, usually in the form of a Blalock-Taussig shunt. Shunts may result in a preferential increase in blood flow to one lung. They also may be associated with significant morbidity and possibly mortality of premature infants. Balloon dilation of the pulmonary valve is reported to improve saturation in early infancy. This report describes two premature infants (weighing, respectively, 1.8 and 1.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(12 reference statements)
1
13
0
1
Order By: Relevance
“…1,[10][11][12][13][14][15][16][17] There is controversy about the outcomes of BPV, and some reports have shown favorable outcomes of palliative BPV in patients with TOF. 13,16,17 Remadevi et al reported a statistically significant improvement in saturation and a high success rate of 87.5%, 17 which is similar to the value of 90.3% (BPV was successful in 28 of 31 patients) obtained in our center. However, there are some reports of poor outcomes such as sustained hypoxemia followed by the need for another palliation surgery or procedural complications, particularly in young infants and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…1,[10][11][12][13][14][15][16][17] There is controversy about the outcomes of BPV, and some reports have shown favorable outcomes of palliative BPV in patients with TOF. 13,16,17 Remadevi et al reported a statistically significant improvement in saturation and a high success rate of 87.5%, 17 which is similar to the value of 90.3% (BPV was successful in 28 of 31 patients) obtained in our center. However, there are some reports of poor outcomes such as sustained hypoxemia followed by the need for another palliation surgery or procedural complications, particularly in young infants and neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of an aberrant left coronary artery from the right coronary artery plays an important part in the surgical approach. In these patients, a Rastelli procedure (RV to PA conduit) is preferred as opposed to a transventricular repair …”
Section: Main Articlementioning
confidence: 99%
“…An aortic root injection will define the coronary and arch anatomy with selective injection in the presence of MAPCAs. Therapeutic interventions in selected cases of unrepaired TOF can include balloon pulmonary valvuloplasty and occasionally RVOT stenting . Regardless, transcatheter approaches may incur the risk of initiating a hypercyanotic spell and be considered with caution in these patients.…”
Section: Main Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The use of catheter-based interventions, consisting primarily of balloon pulmonary valvuloplasty, has been reported in selected infants as a form of early palliation. 24,25 Although it is well recognized that tetralogy represents a surgical disease, the optimal strategy, specifically in regard to the nature and timing of the procedure, remains a subject of interest and ongoing discussion in the field. [26][27][28][29] Potential options are either (1) initial palliation of symptomatic infants with a systemic to pulmonary artery shunt followed by definitive repair at a later time (2-stage approach) or (2) a single-stage primary repair.…”
Section: Management Strategiesmentioning
confidence: 99%